Using Genetic Code Expansion for Protein Biochemical Studies - Chung, Christina Z.; Amikura, Kazuaki; Söll, Dieter (Frontiers in Bioengineering and Biotechnology, 2020)
Protein identification has gone beyond simply using protein/peptide tags and labeling canonical amino acids. Genetic code expansion has allowed residue- or site-specific incorporation of noncanonical amino acids into proteins. By taking advantage of the unique properties of noncanonical amino acids, we can identify spatiotemporal-specific protein states within living cells. Insertion of more than one noncanonical amino acid allows for selective labeling that can aid in the identification of weak or transient protein-protein interactions. This review will discuss recent studies applying genetic code expansion for protein labeling and identifying protein-protein interactions, and offer considerations for future work in expanding genetic code expansion methods.